ANALISA PERANCANGAN SISTEM INFORMASI KOMUNITAS OLAHRAGA FREELETICS SURABAYA MENGGUNAKAN METODE DSDM DAN RUP - Sidharta Sidharta; Wina Permana Sari (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2021)
The Freeletics Surabaya Community does not yet have an information system that can be used to convey information on community activities, health, sports events, and 12 week programs. The 12 week program is a program that members of the community can participate in. In this program, each member will be given a training menu for 12 weeks to work on. Each member who participates in this program is required to provide progress information every week, this information is weight and photos of body changes after doing exercise menu. With the information system, the exercise menu can be accessed via a mobile device and the progress of the exercise results can be uploaded and analyzed according to the needs, namely forming an ideal body and a healthy physique. In addition, it makes it easier for the community to share information on routine activities, 12 week programs, sports activities that can be followed, health information and social activities to the community so that people have other options in terms of health and fun social activities to do. The information system development method is the Dynamic System Development Method which will be integrated with the Rational Unified Process. By using these two methods, it is hoped that the development of information systems can be more effective and efficient. The final result of this research is a web-based information system, which can then be developed into a mobile application-based information system.